Monte Carlo calculation of beam quality correction factors in proton beams using PENH. (17th September 2019) - Gomà, Carles; Sterpin, Edmond
Abstract: This work calculates beam quality correction factors ( ) in both modulated and unmodulated proton beams using the Monte Carlo (MC) code . The latest ICRU 90 recommendations on key data for ionizing-radiation dosimetry were adopted to calculate the electronic stopping powers and to select the mean energy to create an ion pair in dry air ( ). For modulated proton beams, factors were calculated in the middle of a spread-out Bragg peak, while for monoenergetic proton beams they were calculated at the entrance region. Fifteen ionization chambers were simulated. The factors calculated in this work were found to agree within 0.8% or better with the experimental data reported in the literature. For some ionization chambers, the simulation of proton nuclear interactions were found to have an effect on the factors of up to 1%; while for some others, perturbation factors were found to differ from unity by more than 1%. In addition, the combined standard uncertainty in the MC calculated factors in proton beams was estimated to be of the order of 1%. Thus, the results of this work seem to indicate that: (i) the simulation of proton nuclear interactions should be included in the MC calculation of factors in proton beams, (ii) perturbation factors in proton beams should not be neglected, and (iii) the detailed MC simulation of ionization chambers allows for an accurate and precise calculation of factors in clinical proton beams.